1992
DOI: 10.1021/j100201a043
|View full text |Cite
|
Sign up to set email alerts
|

Electronic excitation transfer in concentrated micelle solutions

Abstract: Electronic excitation transport among interacting clusters of chromophores is investigated as a function of chromophore and cluster concentration. The technique of time-correlated single photon counting is employed to obtain time-resolved fluorescence depolarization data on aqueous octadecylrhodamine B/triton X-100 micelle solutions. The time-dependent fluorescence anisotropy, the energy transport observable, is directly compared to a theory developed to model this system. The theory is based on a first-order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…29 The micelles are taken to be dilute, so that electron transfer from a donor on one micelle to an acceptor on another micelle is not considered. How-ever, micelle-to-micelle excitation transfer has been studied in detail, 30,31 and this electron-transfer theory could be extended in an analogous manner.…”
Section: The Model and Monte Carlo Techniquesmentioning
confidence: 99%
“…29 The micelles are taken to be dilute, so that electron transfer from a donor on one micelle to an acceptor on another micelle is not considered. How-ever, micelle-to-micelle excitation transfer has been studied in detail, 30,31 and this electron-transfer theory could be extended in an analogous manner.…”
Section: The Model and Monte Carlo Techniquesmentioning
confidence: 99%
“…4-14͒ apply to systems of random copolymers, 4,6,15-18 micelle surfaces, 5,19,20 and the micellar, lamellar, and cylindrical phases of diblock copolymers, 7,8 making it possible to probe the architecture of a variety of polymer composites at the molecular level. Since the measurement of EET can involve the detection of single fluorescent photons, EET experiments afford a sensitivity that permits probing the configurations of copolymers which are present in a composite at very low concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…We note that the results are particularly relevant for the analysis of experimental data. For example, recent experiments have studied electronic excitation transport among chromophores on micelles. , Analogous experiments could be performed for chromophores that undergo electron transfer, and the results will depend critically on whether the chromophores diffuse significantly on the time scale of the electron-transfer events. Importantly, experimental measurements of diffusion constants for chromophores in micelles have shown that these diffusion constants can be significant .…”
Section: Introductionmentioning
confidence: 99%